Исследования оплодотворения яйцеклетки человека in vitro в 1955 г. - Литвинов, В.В. (Таврический медико-биологический вестник, 2011)
Стаття описує ранні дослідження радянського ученого Г.М. Петрова щодо запліднення людських яйцеклітин в пробірці, які проводилися у Криму в 1950-х роках. Незалежно від Л.Б. Shettles (США), Петров успішно запліднив яйцеклітину людини і виявив розщеплення ембріона і розвиток морули. The article describes the early studies of in vitro fertilization of human oocytes by Soviet scientist G. N. Petrov, which took place in Crimea in the 1950s. Independently of L.B. Shettles (USA), Petrov successfully fertilized human eggs and observed embryo cleavage and morula development.